ACCELERATION TECHNOLOGY ON BOOKS AS CULTURAL MEDIA ON HUMAN COMMUNICATION IN THE ERA OF INTERACTIVE COMMUNICATION - Asthararianty Asthararianty (Desain Komunikasi Visual, Manajemen Desain dan Periklanan (Demandia), 2016)
Dromology is a speed that characterize progress. One of the affected is the culture of reading books. In the past people reading a book in the conventional manner, but in recent years, Internet technology has brought man reading a book in a different way, namely through the e-book. These changes ultimately led to a cultural shift in communication, especially in reading the book. The method used in this research is the study of literature. Results from the study showed that the reading culture (human interactions in a conventional book) has been turned into a reading culture that is synonymous with technology and also acceleration. Characteristics, sensations and experiences have changed. Technology (e-book) has become the new devices in cultured (communication / human interaction).Â Keywords: book, dromology, interpersonal communication, new culture